Recruitment, Training and Human Resource Development for Mr.Blitz Tanjungpinang Employees - Arib Darlicza; Raharani Putri; Silvia Fitriani; Satriadi Satriadi (Dinasti Publisher, 2024)
This study aims to analyze and understand the recruitment, training and development carried out by Mr. Blutz Tanjungpinang in improving the quality of its human resources. This research uses a descriptive qualitative approach. The data collection technique is done through interviews and observation. Data analysis is done through data presentation, data reduction, and concluding. The research results show that the training and development program carried out by Mr. Blitz Tanjungpinang in improving the quality of its human resources is through workshops, seminars on creative, innovative, and fun learning methods, holding independent training by inviting resource persons who are experts in the field, and programmed supervision carried out by managers for employees regarding the achievement of company goals.